2021
DOI: 10.1021/acsptsci.1c00074
|View full text |Cite
|
Sign up to set email alerts
|

Drug and Solute Transporters in Mediating Resistance to Novel Therapeutics in Multiple Myeloma

Abstract: Multiple myeloma remains an incurable malignancy of plasma cells. Novel therapies, notably proteasome inhibitors and immunomodulatory drugs, have improved the survival of multiple myeloma patients; however, patients either present with, or develop resistance to, these therapies. Resistance to traditional chemotherapeutic agents can be caused by cellular drug efflux via adenosine triphosphate (ATP)-binding cassette (ABC) transporters, but it is still not clear whether these transporters mediate resistance to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 135 publications
(345 reference statements)
0
10
0
Order By: Relevance
“…The new derivatives, because of the reduced polarity of the molecule in comparison to melphalan, may have wider delivery strategies. EM-T-MEL, EM-I-MEL, or EM-MORPIP-MEL can be transported to cancer cells by other membrane receptors that are overexpressed in leukemia cancer cells: MCT-1, -2, and -4, for lactate transport; OAT-1, for small, hydrophilic organic anion transport; OCTN-1, FLIPT-1, and OCT-6, for organic cation transport; and OATP1B1 and OATP1B3, for large, hydrophobic anion transport [29]. P2X7R, an ATP-gated ion channel, is widespread in cancer cells and overexpressed in AML.…”
Section: Discussionmentioning
confidence: 99%
“…The new derivatives, because of the reduced polarity of the molecule in comparison to melphalan, may have wider delivery strategies. EM-T-MEL, EM-I-MEL, or EM-MORPIP-MEL can be transported to cancer cells by other membrane receptors that are overexpressed in leukemia cancer cells: MCT-1, -2, and -4, for lactate transport; OAT-1, for small, hydrophilic organic anion transport; OCTN-1, FLIPT-1, and OCT-6, for organic cation transport; and OATP1B1 and OATP1B3, for large, hydrophobic anion transport [29]. P2X7R, an ATP-gated ion channel, is widespread in cancer cells and overexpressed in AML.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, our data suggested that genetic overexpression of SLC19A1 is correlated with inferior prognosis in MM. Previous studies revealed that solute carrier (SLC) transporters play an important role in MM drug resistance, including resistance to novel therapies (44). SLC19A1 belongs to the solute carrier (SLC) group of transporters and is the main mechanism by which folates and antifolate drugs are delivered to mammalian cells and tissues (45).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, methods that down-regulate or inhibit GCS might be expected to re-sensitize cancer cells to therapeutic drugs. In myeloma patients and MM cell lines, treatments with classic chemotherapeutic drugs, such as doxorubicin and melphalan, have been reported to upregulate ABCB1 expression, which contributes to the development of resistance to these drugs ( 198 ). However, it’s unclear if the upregulation of ABCB1 in these cells results from increased GCS.…”
Section: Sphingolipids As Mediators Of Drug-resistance In MMmentioning
confidence: 99%